A Specific Set of Exon Junction Complex Subunits Is Required for the Nuclear Retention of Unspliced RNAs in Caenorhabditis elegans - Shiimori, Masami (American Society for Microbiology, 2013)
The exon junction complex (EJC) is highly conserved in many organisms and is involved in various steps of mRNA metabolism. During the course of investigating the role of EJC in the germ line sex determination of the nematode Caenorhabditis elegans, we found that depletion of one of the three core subunits (Y14, MAG-1, and eukaryotic translation initiation factor 4III [eIF4AIII]) or one auxiliary subunit (UAP56) of EJC resulted in the cytoplasmic leakage of unspliced RNAs from almost all of the C. elegans protein-coding genes examined thus far. This leakage was also observed with the depletion of several splicing factors, including SF3b, IBP160, and PRP19, all of which genetically interacted with Y14. We also found that Y14 physically interacts with both pre-mRNA and spliceosomal U snRNAs, especially U2 snRNA, and that the interaction was abolished when both IBP160 and PRP19 were depleted. Our results strongly suggest that a specific set of EJC subunits is recruited onto introns and interacts with components of the spliceosome, including U2 snRNP, to provide a critical signal for the surveillance and nuclear retention of unspliced RNAs in C. elegans.